CFD analysis and optimization of vane angle of cyclone separator. (2021) - Rathish, R.; Krishnakumar, P.; Anandh, G.; Kumar, V. Bharath; Bharathkumar, T.; Dhanapal, S.
Abstract: The moisture in the compressed air causes severe damages to the devices that uses compressed air. Cyclone separator is used to separate moisture from the compressed air. Computational fluid dynamics is used as a tool to analyse the cyclone separator where a flow of compressed air is passed through the inlet then the compressed air is made to strike the vane and thus the swirling movement is created. By this an internal flow is made up. Fluid flows, pressure of compressed air, velocity of compressed air are the parameters that are considered here. The above said parameters are kept constant and by changing the vane in different angles, the velocity, pressure, and path line in the separator are simulated. The pressure drop obtained from the analysis according to different angles of vane is compared and the vane angle that produces the highest-pressure drop is found by the help of computational fluid dynamics. The velocity of the compressed air flow is also checked whether it is below the erosion velocity limit so that the erosion of the parts inside the cyclone separator will be predicted. The vane angle that produces the maximum pressure drop and velocity lesser than the erosion velocity limit is the most efficient in removing the moisture from the compressed air.